Stress Management and Subjective Well-Being of the Health Workers Dealing with Covid-19 - Almas, Husniyah; Sunarti, Euis; Johan, Irni Rahmayani (Pakistan Journal of Humanities and Social Sciences, 2022)
The COVID-19 pandemic has had an impact on family well-being. The impact will depend on how the family manages stress during an unstable situation such as the COVID-19 pandemic. The study aimed to analyze the effect of family and work characteristics, sources of stress, coping strategies, and stress symptoms on the subjective well-being of families. This study uses an online questionnaire as a data collection tool. Data collection was carried out in DKI Jakarta that involved 100 health workers (60 health professionals and 40 health support personnel). Processing and analyzing data use Microsoft Office Excel 2016, SPSS 25.0, and SmartPLS 3.3.2. Data analysis performed were descriptive, independent sample t-test, and SEM analysis. According to the results, health support workers are more likely to feel the source of problems due to change and work compared to professional health workers. The lower stressor and stress symptoms increase the family’s subjective well-being. Furthermore, stressor and stress symptoms are intermediate variable that affects subjective family well-being. The results of this study can be used as a consideration for intervention for related parties in the event of a new pandemic situation in the future.